The Use of Spanish in US Sports Information (Global Journal of Human-Social Science, 2024)
The article is about the influence of Spanish in the US through sports information. There was a first moment related to the first emigration, in the search for that first American dream. Today, professionals come from a more globalized environment. Among the levels, the lexicalsemantic level plays an important role, with a trend in recent years towards leveling. American sports information in Spanish currently exerts an influence on the rest of society.
Keywords: sport; information; athletes; Spanish; English